Examining corruption in biblical texts through deontological and virtue ethical codes - Diko, Mlamli (Verbum et ecclesia, 2024)
In contemporary contexts, the understanding of corruption is different from what is illustrated in biblical narratives. Conversely, some of the ways in which corruption is contested and addressed in biblical narratives prove to be applicable in contemporary contexts, particularly in the jurisdictions of leadership and governance, politics and community service. Therefore, this article aims to critique how corruption is (re)produced in the Bible. The objective is to underline that whereas the Bible is a primordial narrative, it mirrors some challenges that adversely affect the contemporary contexts, with special reference to corruption. To advance the aim of this article, deontological and virtue ethical codes are applied as theoretical frameworks to uncover corruption within the Bible. This article makes three notable findings. Firstly, corruption undermines public trust, while it erodes self-reliance in the rule of law. Secondly, corruption is depicted as a moral and spiritual decomposition that erodes the foundational values of morality and conformity to God. Thirdly, the Bible depicts corruption as a transgression of the commandments and moral ethos. Nevertheless, in response to corruption, there are instances in which God pronounces verdicts and imposes retribution. The conclusion underlines that the comprehension of corruption is intricately interwoven and requires scholarly dialogues to unmask any covert denotations. Intradisciplinary and/or interdisciplinary implications: This article is interdisciplinary as it elicits discernments from the theological discipline and ethical codes that are interlaced in social, economic and political dimensions. The integration of perceptions from philosophy, ethics and literary critique warrants a worthy discourse that forms juxtaposition.